A Fatal Case of Diffuse Alveolar Hemorrhage in the Setting of Systemic Lupus Erythematosus: A Case Report and Review of Noninfectious Causes of Acute Pulmonary Hemorrhage in Adults. (11th February 2021) - Lundgren, Mia C.; Molitor, Jerry A.; Spilseth, Benjamin; Adeyi, Oyedele
Abstract : Systemic lupus erythematosus (SLE) is an autoimmune connective tissue disease, characterized by autoantibody production and immune complex formation, that has the potential to affect virtually any organ. Pleuropulmonary involvement occurs in 50–70% and commonly manifests as pleuritis and pleural effusion. Diffuse alveolar hemorrhage (DAH) is a rare manifestation of SLE. Most cases of DAH occur in young adults with an underlying autoimmune disease such as systemic vasculitis or Goodpasture syndrome. SLE is typically lower on the list of initial differential diagnoses of DAH due to its rarity compared to other etiologies. We present a case of a patient with dyspnea on exertion, dry coughs, lower extremity edema, and intermittent periorbital edema who ultimately succumbed to respiratory failure secondary to DAH in the setting of SLE. The diagnosis of SLE was suspected clinically and confirmed at autopsy due to her rapid clinical deterioration. DAH requires prompt intervention, and management is guided by the underlying disease process. SLE is a potentially treatable disease; therefore, timely diagnosis is important in order to exclude other noninfectious causes of DAH (reviewed in this report) and to initiate appropriate therapy.